Allozyme Analysis For Assessing Genetic Variation In The Species Bactrocera Diversa And B. Zonata (Diptera: Tephritidae) - RASHMI SINGH; AKANKSHA SINGH; UMA R. AGRAWAL; R.R.TEWARI (International Journal of Pharma and Bio Sciences, 2011)
Allozyme analysis was used to assess genetic variability in tephritid fruit fly Bactrocera diversa and B. zonata. In our experimental conditions, allozyme analysis at twelve enzyme loci scores twenty one putative alleles. The amount of mean observed heterozygosity (HO) was 0.22 and 0.28 and amount of mean expected heterozygosity (HE) was 0.28 and 0.37, in B. diversa and B. zonata, respectively. The amounts of observed and expected heterozygosity were found to be higher as compared to the general low level of variability found in tephritid flies. Nei’s genetic identity and distance value reveals very close similarity between the two species.